CFD Investigation of Empty Flanged Diffuser Augmented Wind Turbine - Jabbar Al-quraishi, Balasem Abdulameer; Asmuin, Nor Zelawati; Nasir, Nurul Fitriah; Abdul Latif, Noradila; Taweekun, Juntakan; Mohd, Sofian; Mohammed, Akmal Nizam; Abd al-wahid, Wisam (International Journal of Integrated Engineering, 2020)
Enclosing a wind turbine within a Flanged diffuser is an innovative mean to increase the power harvested by turbine blades and it is among the most effective devices for increasing wind turbine energy. The geometric parameters of the empty flanged diffuser contribute efficiently to increase mass flow in the diffuser, hence improve the turbine performance. The study presents developed models of the geometrical parameters of an empty flanged diffuser that suitable for a scaled-down (1-6.5) horizontal axis wind turbine, the geometry parameters were involved the diffuser length, diffuser angle, flange height and flange angle. The geometrical models were verified and CFD investigated in 2-D and 3-D domains. Results obtained from CFD simulations show that when using a compact size of flanged diffuser within optimum geometrical parameters can give well acceptable for flow velocity increase at suggested place for the turbine rotor install where the increase in flow velocity is due to lower pressure at the outlet of the diffuser. As there is also a significant effect of the flange angle on increasing the flow velocity inside the diffuser where the rate of increase in wind velocity at turbine position was calculated for two flange angles (0 ÌŠ and 5 ÌŠ ) . In another hand, the results also provided information on the velocity contours and velocity streamlines around diffuser geometry.